Identity and its political manipulation in Syria - Sharkawy, Nada Yasser (AUC Knowledge Fountain, 2017)
This research takes a social constructivist approach in order to analyze how identity is used as a political tool, leading to the current civil war in Syria. Identity plays a great role in the political scene in Syria ever since the French Mandate, in which the state was broken into an ethnofederal system. Subsequently the French employed a divide and conquer tactic in order to prevent the unity of Syria therefore making it easier to establish control. Later on, after multiple coups, Hafiz Al-Assad rose to power along with a select group of trusted individuals from his family, tribe, and sect. He then proceeded to create a system whereby the minority Alawites ruled the country. Despite his use of Pan-Arabism, as a means of uniting the country behind a Ba’th ideology which advocated equality amongst the sects, he ensured that the state’s coercive apparatuses remained loyal to the Alawite regime. His son, Bashar Al-Assad, did not change the system in place and he actually reinforced. Both Hafiz and Bashar used identity through framing the situation as either an Alawite regime or a radical Islamist regime, therefore gaining the support of other minorities. Furthermore, both used favoritism policies enabling a select few Sunnis and other sects to gain economic privileges even though such a tactic caused resentment within sects and between the different sects. The Arab Spring has provided an opportunity for the local identities to be reactivated. Years of political maneuvering have resulted in a conflict which evolved into a sectarian conflict driven by anger, fear and resentment. The collapse of the Syrian state has caused a fall of the patronage networks, thus reinforcing the individual reliance on the local identity for basic services. This conflict has been further exacerbated through the involvement of international powers fighting a proxy war as a means of furthering their own interests through aiding certain groups and thus creating an imbalance in the political scene.